Conversation with Mark Mizruchi:“There is Very Little Organizational Theory Left in Sociology Departments” - Mark S. Mizruchi (Journal of Economic Sociology, 2015)
Prof. Mizruchi was interviewed by Igor Chirikov, senior research fellow at the National Research University Higher School of Economics in Moscow. In the interview, Prof. Mizruchi was asked about the evolution of his research interests and peculiarities of his approach to teaching organizational theory. Prof. Mizruchi also described how he became acquainted with organizational sociology. Within his winding career trajectory from Statistical Analyst at Albert Einstein College of Medicine to Professor of Sociology at the University of Michigan, Mark Mizruchi has witnessed the development of both organizational theory and sociology of organizations and their division into institutionally separate subfields. Whether such fragmentation is methodologically important, it certainly affects the teaching process of organizational theories to students and the future of the whole field by shifting its research focus from broad and theoretical issues to more narrow and applied problems. In addition, Prof. Mizruchi shared the main ideas of his recent award-winning book (The Fracturing of the American Corporate Elite) and details of the creative writing process. In the final part of the conversation, Prof. Mizruchi told the story of how the Interdisciplinary Committee on Organizational Studies (ICOS) was established and how it influences research and teaching processes at the University of Michigan.